Absent or diminished pedal pulses and estimated GFR decline in patients with diabetic kidney disease. (1st January 2019) - Subramanian, Nivetha; Xu, Jennifer; Sayyed Kassem, Laure; Simonson, Michael; Desai, Niraj
Abstract: Background: Peripheral artery disease (PAD) is a complication of type 2 diabetes that leads to critical limb ischemia and amputation. We tested whether absent or diminished pedal pulses (ADPPs) predicts subsequent renal functional decline in patients with diabetic chronic kidney disease (CKD). We also examined the association between urinary biomarkers and ADPP as well as worsening CKD. Methods: Using a prospective longitudinal design, we studied 91 patients with type 2 diabetes and estimated glomerular filtration rate (eGFR) from 7 to 146 mL/min/1.73 m 2 . Baseline pedal pulses were assessed by standardized history and physical examination. The primary endpoint was decline in eGFR >30%. Potential confounders of the relationship between pedal pulses and eGFR were assessed by multivariable logistic regression. Results: Of 91 participants (median age 58 (range 30–83); median eGFR 72.4 ± 33.4 mL/min/1.73 m 2 ), 43% had at least one ADPP. Baseline ADPP associated with increased risk of greater than 30% decline in eGFR (OR= 3.67, p = .004). This association remained significant (OR = 3.09, p = .029) after adjustment for traditional risk factors of renal function decline in diabetic kidney disease (DKD). In addition, urinary endothelin-1 (ET-1) was higher among patients with ADPP ( p =.0006) and associated with eGFR decline greater than 30% (adjusted OR = 1.81, p = .035). Conclusions: ADPP is a strong predictor of decline in renal function in type 2 diabetes. Patients with type 2 diabetes and abnormal pedal pulses should be screened for DKD and monitored closely for progression of CKD.